Effects of Supplementation of Aloe vera (Aloe barbadensis) and Tulsi (Ocimum sanctum) as Feed Additives on Performance of Broiler Chickens - Tanwar, Reenu; Sharma, Vishnu; Karnani, Monika; Choudhary, Sheela; ., Manju (Indian Journal of Animal Nutrition, 2022)
A study was carried out to investigate the efficacy of dietary supplementation of Aloe vera (Aloe barbadensis) and Tulsi (Ocimum sanctum) powder as a feed additive on growth performance, feed consumption, and feed conversion efficiency of broilers. The experiment was conducted in a completely randomized design with a total of 240-day-old broiler chicks (Vencobb) randomly assigned to four treatment groups with four replicates having 15 birds in each replicate for a period of five weeks. Birds were offered the maize-soybean based basal diet. The treatment groups consisted of control group (T1) fed only basal diet without additive, T2 supplemented with 0.5% Aloe vera powder, Â T3 supplemented with 0.5 % Tulsi powder and T4 supplemented with 0.25 % Aloe vera powder + 0.25 % Tulsi powder in the diet. No significant effect on feed intake was observed among different groups due to supplementation of feed additives. The final body weight and body weight gain were significantly (P